8t-(5t+3)=12

Simple and best practice solution for 8t-(5t+3)=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8t-(5t+3)=12 equation:



8t-(5t+3)=12
We move all terms to the left:
8t-(5t+3)-(12)=0
We get rid of parentheses
8t-5t-3-12=0
We add all the numbers together, and all the variables
3t-15=0
We move all terms containing t to the left, all other terms to the right
3t=15
t=15/3
t=5

See similar equations:

| 4x^2+12x+48=0 | | F(×)=56x^2+65x-35 | | 2=2(m-16) | | 7+7b–2–15b+b=4b–5–11b+2+10 | | 2(3x–1)=-6x–2 | | 7x+8+2x-3=5x+7+4x-3 | | 17^-x+4=2^-7x | | 3(7x+5)=2 | | D=13x+15 | | -8d+-7d=15 | | 52=10x+7 | | 59+x=90 | | 10x-2=4(-x-10) | | 8e=36 | | 3g-7g=-4 | | 1/3(x+3)=12 | | 7-2-1/7-3x/7=2x/3-1/3 | | 3x-7-(9x-6)=15 | | 8b+8b=–12 | | 915=1500-35x | | 12k-8k=16 | | Xx3/8=-15/32 | | 7+n×2=20 | | -4=-4(r-19) | | 24=3+(x-1)2 | | √x+√x+8=2√x | | 8(y+2)=5(2y-4) | | 4(6x-1)^2-5=223 | | 4^3x-1=32 | | -4(m+12)=-8 | | .4x+56=60 | | 10=z−2+7 |

Equations solver categories